EFEKTIFITAS EKSTRAK DAUN AFRIKA (Vernonia amygdalina delile) DAN DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) TERHADAP ZONA HAMBAT PERTUMBUHAN Staphylococcus aureus - Lailatul Chusniyah; Susie Amilah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
Has conducted research to determine the influence of Afrika Leaf Extract (Vernonia amygdalina delile) and Binahong Leaf Extract (Anredera cordifolia (Ten.) Steenis) against Staphylococcus aureus growth inhibition zone. The purpose of this study was to determine the effectiveness of Afrika leaf extract (Vernonia amygdalina delile) and leaves Binahong (Anredera cordifolia (Ten.) Steenis) against Staphylococcus aureus growth inhibition zone. The material used in this study is the bacterium Staphylococcus aureus, variations in the concentration of leaves and leaf binahong Afrika. The method used in this research is the diffusion disc with a completely randomized design (4 treatments 6 replications). Leaves Afrika have active compounds are efficacious as antibacterials are flavonoids, tannins, saponins and terpenoids. Binahong Leaf Extract has antibacterial compounds are flavonoids, tannins, alkaloids and essential oils. The results showed that the leaf and leaf afrika binahong with concentrations of 0%, 40%, 60% and 80%. Has an influence on the growth inhibition zone of Staphylococcus aureus. Keywords: inhibition zone, extract, Afrika leaf, leaf binahong, Staphylococcus aureus